2013
DOI: 10.14713/pcsp.v9i3.1826
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Controversies in the Application of a Modified Version of Cognitive Behavior Therapy for Social Anxiety Disorder

Abstract: In their comprehensive case study, Jensen, Hougaard, and Fishman (2013) examined the microlevel mechanisms of change for a socially anxious client who underwent one-week of intensive group-based cognitive behavioral therapy (CBT) and experienced rapid symptom improvement. Our commentary focuses on two key components in the cognitive model of social anxiety, which this study highlights -the role of safety behaviors and interrogating the social environment, as well two topics that are applicable to anxiety treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Therefore, to control for possible distribution of practice/training effects, which have been shown to impact retention of new skills and information learned (e.g., Miller & Binder, 2002), we also controlled for within-therapist session density (i.e., mean number of sessions per month). That is, past work has indicated that either more concentrated learning (Tsao & Craske, 2000) or distributed learning (i.e., the same content, but presented and practiced over a longer, more spaced out period of time; Rogojanski & Rego, 2013; Storch et al, 2008) can improve memory consolidation and skills retention. To account for potential variability among therapists in the effect of time, we also included the random slopes for time (i.e., within-therapist session number) in all analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, to control for possible distribution of practice/training effects, which have been shown to impact retention of new skills and information learned (e.g., Miller & Binder, 2002), we also controlled for within-therapist session density (i.e., mean number of sessions per month). That is, past work has indicated that either more concentrated learning (Tsao & Craske, 2000) or distributed learning (i.e., the same content, but presented and practiced over a longer, more spaced out period of time; Rogojanski & Rego, 2013; Storch et al, 2008) can improve memory consolidation and skills retention. To account for potential variability among therapists in the effect of time, we also included the random slopes for time (i.e., within-therapist session number) in all analyses.…”
Section: Methodsmentioning
confidence: 99%